AUTOPSIA PSICOLÓGICA EN LOS CASOS PENALES DE HOMICIDIO Y SUICIDIO OCURRIDOS EN LA CIUDAD DE MONTERÍA DURANTE EL PERIODO 2010–2015 (2023)
The overall objective of this study is to analyze the importance of the application of the psychological autopsy technique in doubtful homicide and suicide cases that occurred in Montería, during the period from 2010 to 2015